Effectiveness of Marjan Advertising on YouTube Using EPIC Model - Abi Muhammad Fauzan (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
YouTube is one of the advertising media for brands that advertise in the form of videos, such as Marjan. Marjan is a local syrup brand produced by PT Lasallefood Indonesia. However, there are issues that appear in the comments section on YouTube which have an impact on the decrease in views of Marjan advertising content on YouTube in 2024. For this researchers are interested in researching the effectiveness of Ramadan Marjan advertisements on YouTube using the EPIC Model (Empathy, Persuasion, Impact, Communication). This research uses a type of quantitative research with a survey method through an online questionnaire through Google Form. The distribution of online questionnaires through Google Form was carried out in this study to 120 respondents who were Marjan consumers with domiciles in Jabodetabek and had seen Marjan's Ramadan advertisements on YouTube. Sampling was carried out using non-probability sampling method through purposive sampling technique. The analysis techniques used in this study are descriptive analysis, simple tabulation analysis, and average score. Based on the results of the study, all dimensions of the EPIC Model are declared effective with a score of 3.12. This is supported by the score of each dimension such as empathy with a value of 3.26 which is included in the very effective category, and other dimensions that are included in the effective category such as persuasion with a value of 3.08, impact 3.15, and communication 3.01.